Preoperative Naples prognostic score is a reliable prognostic indicator for newly diagnosed glioblastoma patients - Li, Junhong; Yang, Wanchun; Yuan, Yunbo; Zuo, Mingrong; Li, Tengfei; Wang, Zhihao; Liu, Yanhui (Frontiers in Oncology, 2022)
Background Glioblastoma (GBM) accounts for approximately 80% of malignant gliomas and is characterized by considerable cellularity and mitotic activity, vascular proliferation, and necrosis. Naples prognostic score (NPS), based on inflammatory markers and nutritional status, has a prognostic ability in various cancers. In the current study, we aim to explore the prognostic value of operative NPS in GBM patients and compare the prognostic ability between NPS and controlling nutritional status (CONUT). Materials and methods The retrospective analysis was carried out on consecutive newly diagnosed GBM patients who had underwent tumor resection at West China Hospital from February 2016 to March 2019. All statistical analyses were conducted using SPSS software and R software. Results A total of 276 newly diagnosed GBM patients were enrolled in the current study. Overall survival (OS) (p < 0.001) and tumor location (p = 0.007) were significantly related to NPS. Serum albumin concentrate, cholesterol concentrate, neutrophil-to-lymphocyte ratio, lymphocyte ratio, and CONUT score were all significantly associated with NPS (p < 0.001). The Kaplan–Meier curve indicated that NPS (log-rank test, p < 0.001) and CONUT score (log-rank test, p = 0.023) were significantly associated with OS. Multivariate Cox regression revealed that both NPS and CONUT score served as independent prognostic indicators. The prognostic model with NPS had the strongest prognostic capability and best model-fitting. Conclusion In the current study, NPS is found as an independent prognostic indicator for patients with newly diagnosed GBM, and the prognostic ability of NPS is superior to CONUT score.